2011
DOI: 10.1080/03079457.2011.588197
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility ofBrachyspiraspp. isolated from commercial laying hens and free-living wild mallards (Anas platyrhynchos)

Abstract: In vitro antimicrobial susceptibility to tylosin, valnemulin, tiamulin, doxycycline, lincomycin and ampicillin was investigated by broth dilution in 48 Brachyspira spp. isolates from commercial laying hens (n030) and free-living wild mallards (Anas platyrhynchos) (n018). Presumed pathogens (Brachyspira alvinipulli, Brachyspira intermedia, Brachyspira pilosicoli), commensals (Brachyspira murdochii, Brachyspira innocens, ''Brachyspira pulli''), and isolates of undetermined species affiliation were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…These results were not unexpected and are in accord with those obtained by Jansson et al for different Brachyspira spp. isolated from wild-living mallards [12], likely due to the limited environmental exposure to antimicrobials among intestinal spirochaetes originating from wild birds. However, these values could be used as a baseline for monitoring the antimicrobial susceptibility of avian “ B. hampsonii ” isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were not unexpected and are in accord with those obtained by Jansson et al for different Brachyspira spp. isolated from wild-living mallards [12], likely due to the limited environmental exposure to antimicrobials among intestinal spirochaetes originating from wild birds. However, these values could be used as a baseline for monitoring the antimicrobial susceptibility of avian “ B. hampsonii ” isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Although information on the antimicrobial susceptibility of Brachyspira spp. of avian origin is scarce, decreased susceptibility to β-lactams has been described in B. pilosicoli isolates obtained from wild-living mallards [12]. This information points towards the necessity of testing the antimicrobial susceptibility of enteropathogenic Brachyspira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Valnemulin has been used extensively to treat respiratory tract infection in swine, calf and poultry (Stipkovits et al ., ; Tzika et al ., ; Jansson & Pringle, ). Previous studies showed that valnemulin had great antibacterial activities against mycoplasma, spirochetes, gram‐positive bacteria, and some fastidious gram‐negative bacilli (Karlsson et al ., ; Ohya & Sueyoshi, ).…”
Section: Introductionmentioning
confidence: 97%
“…The MIC was recorded as the lowest concentration of ampicillin that inhibited growth. An MIC of 32 or more was used as being indicative of a lack of susceptibility (Jansson & Pringle, 2011).…”
Section: Antimicrobial-susceptibility Testingmentioning
confidence: 99%
“…This enzyme contributes to penicillin resistance in the spirochaete, and in particular confers resistance to oxacillin, benzylpenicillin and ampicillin by cleaving the b-lactam ring (MezianeCherif et al, 2008). Following the original description of the gene, three variants (bla , bla OXA-137 and bla ) have been described in other strains of B. pilosicoli isolated from humans, pigs and birds (MortimerJones et al, 2008;Jansson & Pringle, 2011). These enzymes are unique to B. pilosicoli and constitute the 'OXA-63 group', with the nearest neighbour being OXA-85 from Fusobacterium nucleatum subsp.…”
Section: Introductionmentioning
confidence: 99%